2006
DOI: 10.1016/j.drugalcdep.2006.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant use and disorders among adults in the United States

Abstract: Objective-To examine the patterns of adult inhalant use and correlates of inhalant use disorder.Method-We drew study data from the 2002 and 2003 National Surveys on Drug Use and Health (NSDUH). We used logistic regression to identify the characteristics associated both with inhalant use and inhalant use disorder.Results-One in ten of all adults had used an inhalant at least once in their lives, and 0.5% used one in the past year. Among all past year inhalant users, 8% met the criteria for an inhalant use disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
0
38
0
8
Order By: Relevance
“…Compton et al (1994) identifi ed a signifi cant association between inhalant use and antisocial personality disorder (ASPD) in a treatment sample of 545 St. Louis illicit drug users; 64% of lifetime inhalant users met DSM-IV ASPD criteria, compared with 35% of inhalant nonusers. Wu and Ringwalt (2006) reported that 2.6% of total respondents to the 2002/2003 National Survey on Drug Use and Health had been booked or arrested in the prior year, compared with 49.9% of lifetime inhalant users.…”
mentioning
confidence: 99%
“…Compton et al (1994) identifi ed a signifi cant association between inhalant use and antisocial personality disorder (ASPD) in a treatment sample of 545 St. Louis illicit drug users; 64% of lifetime inhalant users met DSM-IV ASPD criteria, compared with 35% of inhalant nonusers. Wu and Ringwalt (2006) reported that 2.6% of total respondents to the 2002/2003 National Survey on Drug Use and Health had been booked or arrested in the prior year, compared with 49.9% of lifetime inhalant users.…”
mentioning
confidence: 99%
“…Uçucu maddeleri içeren ürünler yasaldır ve kolay bulunur. Bu nedenle, çocuk ve ergenler kolay ula-şır, riskli gruplarda bağımlılık gelişimini kolaylaştırır (2,3,5). Uçucu madde kullanımı başlangıç yaşı 6'ya kadar inebilir, 14-15 yaşları en sık kullanılan dönemdir ve yaş ilerledikçe kullanım azalır (2,5,6).…”
Section: Introductionunclassified
“…Bu nedenle, çocuk ve ergenler kolay ula-şır, riskli gruplarda bağımlılık gelişimini kolaylaştırır (2,3,5). Uçucu madde kullanımı başlangıç yaşı 6'ya kadar inebilir, 14-15 yaşları en sık kullanılan dönemdir ve yaş ilerledikçe kullanım azalır (2,5,6). Kızlarda uçucu madde bağımlılığı küçük yaşlarda daha fazlayken, yaş ilerledikçe erkekler öne geçer; 17 yaşına gelindiğinde, uçucu madde bağımlılık oranı, kadınlarda %1.1, erkeklerde %2.2'dir (5).Türkiye'de yaşam boyu uçucu madde kullanım oranı %8.8 dir (7).…”
Section: Introductionunclassified
See 2 more Smart Citations